The Development of Computer Inventory Management System for Faculty of Science and Technology Nakhon Ratchasima Rajabhat University - KhaKhum, Thamonwannapohn (Journal of Applied Informatics and Technology, 2024)
The objectives of this study were to: 1) develop a computer inventory management system for the Faculty of Science and Technology 2) to study the evaluation of the system efficiency from 3 experts 3) to study the evaluation of user satisfaction with the use of the sample group. The selection of the sample group is based on the purposive sampling technique. By selecting from the support personnels who are involved in managing the curriculum equipment under the Faculty of Science and Technology, Nakhon Ratchasima Rajabhat University, a total of 30 people were selected. The preliminary test results show that the system is practical and can be beneficially utilized. The evaluation of the system’s performance by experts yielded an average rating at a high level, with a mean score ( ) of 4.35 and a standard deviation of 0.55. The average results classified by aspect found that the ease of use aspect is at the highest level. The performance aspect meets the requirement aspect and Information security aspect are at a high level of satisfaction. The satisfaction evaluation from the sample group regarding system usage also scored high, with an average of ( ) 4.31 and a standard deviation of 0.58. The average results classified by aspect found that satisfaction with the system Service aspect of officials is at a high level.